The Lucas Critique, Policy Invariance and Multiple Equilibria - Farmer, Roger E. A. (Review of Economic Studies, 1991)
The Lucas Critique of Econometric Policy Evaluation argues that the parameters of econometric models are subject to theoretical cross-equation restrictions which follow from the fact that the endogenous variables of the models are chosen optimally by forward-looking agents. In this paper I argue that these facts alone are insufficient to generate such restrictions. I present an example of a model in which there exist multiple stationary rational expectations equilibria one of which is supported by a process-invariant forecast rule. Immunity to the Lucas Critique is proposed as a selection criterion in models with multiple equilibria.